Gamma-ray irradiation induced polymorphism in Echinacea purpurea revealed by RAPD markers - AGUSTINA PUTRI CAHYANINGSIH; NITA ETIKAWATI; AHMAD YUNUS (Smujo International, 2025)
Abstract. Cahyaningsih AP, Etikawati N, Yunus A. 2025. Gamma-ray irradiation induced polymorphism in Echinacea purpurea revealed by RAPD markers. Nusantara Bioscience 17: 289-297. One of the major challenges in the development and cultivation of Echinacea purpurea in Indonesia is the narrow genetic diversity and the lack variation of local accessions, which restricts breeding potential to produce superior varieties with improved traits in terms of morphological characteristics and phytochemical content as medicinal ingredients. To overcome this challenge, gamma-ray irradiation methods can be used as an effective tool to induce mutations and increase genetic variability. This study investigated the impact of gamma irradiation on the genetic diversity of E. purpurea using Random Amplified Polymorphic DNA (RAPD) markers. The seeds of E. purpurea were irradiated using gamma-ray with irradiation doses of 0 Gy (control), 20 Gy, 40 Gy, and 60 Gy. Nine RAPD primers, including OPA-10, OPA-16, OPA-18, and OPA-19, were used to amplify DNA segments. The binary data obtained from the electrophoresis visualization for each treatment were analyzed using the Dice similarity index to calculate the similarity index. Dendrogram construction were performed using the NTSYS. The analysis revealed a significant increase in genetic diversity at doses of 40 Gy and 60 Gy, with 58.04% of the total bands showing polymorphism across all treatments. The 60 Gy treatment, in particular, resulted in the highest genetic dissimilarity compared to the control, indicating a dose-dependent response. The similarity coefficients between control and irradiated plants ranged from 63.7% (20 Gy) to 84.4% (0 Gy), with a noticeable trend toward greater genetic differentiation as the irradiation dose increased. These findings suggest that gamma irradiation effectively induces genetic variation in E. purpurea, which could be harnessed for mutation breeding programs aimed at improving desirable traits such as phytochemical production. However, further studies with larger sample sizes and long-term evaluation are needed to assess the stability of these mutations and their potential for incorporation into breeding programs. This study provides preliminary evidence supporting the use of gamma irradiation in enhancing genetic diversity and its potential application in breeding superior E. purpurea varieties with improved agronomic or medicinal traits.